The Effect of Argument Driven Inquiry Learning Models on Scientific Argumentation Skills and Higher Order Students on The Topics of Acid Base - M. Agung Satriya; Sri Atun (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of the argument driven inquiry learning model on the simultaneous scientific argumentation skills and higher order thinking skills in students on the topic of acid base. The research uses a quasi-experimental method with a pretest-posttest control group design. This research was conducted on 137 students of class XI MIPA at a high school in Palembang. Sampling was done by the simple random sampling technique. The results of the study showed that there was a significant effect of the argument driven inquiry learning model on the scientific argumentation skills and higher order thinking skills of the students on the topic of acid base. There is an effective contribution of the application of the learning model of argument driven inquiry on the topics of acid base to enhance the scientific arguments skills and the higher order thinking skills of students at the same time of 18.90%. In general, the students gave a positive response to the application of the argument driven inquiry learning model to enhance the scientific argumentation skills and higher order thinking skills.